People, profit and politics state-civil society relations in the context of globalization - Wui, Ma. Glenda Lopez; Tadem, Teresa S. Encarnacion (Quezon City Third World Studies Center, College of Social Sciences and Philosophy, 2006)
"This research project on state-civil society relations in the context of globalization analyzes the relations between the Philippine state and selected civil-society actors in the context of globalization. It focuses on four sectors: the Benguet vegetable, hog, garment, and telecommunications industries. These sectors are widely known to have been affected by economic liberalization--negatively in the case of the first three, and positively in the case of the telecommunications industry. The project investigates two interrelated aspects of state-civil society relations: 1) how civil-society actors engage with official state agencies through various formal and informal strategies of dialogue, negotiation, and bargaining; and 2) the extent to which civil-society actors have been able to influence governmental policy making."--Introduction.
Foreword / Walden Bello -- Preface -- Introduction / Teresa S. Encarnacion Tadem -- Mobilizing against vegetable importation / Sharon M. Quinsaat -- Protests and perceived threats in the hog industry / Joel F. Ariarte, Jr. -- Confronting the challenges in the garment industry / Ma. Glenda S. Lopez Wui -- Balancing consumer and corporate interests in the telecommunications industry / Ronald C. Molmisa -- Conclusion : palliatives for "globalization with a human face" / Teresa S. Encarnacion Tadem.
"Published in cooperation with the United Nations Development Programme-Philippine Office."
Keywords: Industries -- Philippines -- Benguet -- Case studies; Globalization -- Philippines -- Benguet -- Case studies; Civil society -- Philippines -- Benguet -- Case studies; Industrial relations -- Philippines -- Benguet -- Case studies